DIFFERENTIAL SENSITIVITY OF CHICKPEA GENOTYPES TO SALICYLIC ACID AND DROUGHT STRESS DURING PRE-ANTHESIS: EFFECTS ON TOTAL CHLOROPHYLL, PHENOLICS, SEED PROTEIN AND PROTEIN PROFILING - PATEL, PRADEEP KUMAR; A. HEMANTARANJAN (The Bioscan, 2013)
The work was conducted with the purpose to evaluate the effect of salicylic acid (SA) under drought stress on chlorophyll pigment, phenolics, seed protein and protein profile in four chickpea (Cicer arietinum L.) genotypes (i.e., Tyson, ICC 4958, JG 315 and DCP 92-3). The experiment was carried out in a complete randomized design with three replications. Drought stress was imposed during the pre-anthesis phase. Reduction in relative injury was observed in plants treated with SA at the threshold level of 1.5mM. Drought stress reduced the total chlorophyll and percentage of seed storage protein, where increases the level of total phenolics content were observed under drought stress and this was further induced by SA. The genotype ICC 4958 perform better than Tyson, JG 315 and DCP 92-3 under drought stress with SA treatment. Moreover, it is also noteworthy that drought did not change significantly the 1-D protein profile of chickpea genotypes. This suggests that chickpea could be induced to tolerate drought using 1.5mM of SA.